Analisis Kandungan COD dan BOD di Tiga Titik Lokasi Sungai Patrean Manding Sumenep - Ulfatun Hasanah; Nor Hayati; Tinwarotus Zahro; Rif’atul Hasanah; Nurul Inayah (Fakultas MIPA Universitas Nahdlatul Wathan Mataram, 2023)
The Patrean River is one of the rivers that flows in several locations in Sumenep District including Manding, Batuputih, Dasuk, Gapura and Kota sub-districts. This river is heavily flowed by domestic waste and industrial waste. The presence of such waste can cause a decrease in water quality characterized by an increase in Biological Oxygen Demand (BOD) and Chemical Oxygen Demand (COD). The purpose of this study was to determine the BOD and COD content at three locations of the Patrean river, and to assess the pollution status using the pollution index method based on Government Regulation No. 82 of 2021. Sampling was carried out in three locations (upstream, middle, and downstream), this research method used survey and experimental methods. The results of the calculation of COD values in Patrean River waters at upstream, middle and downstream points are 12.75 mg/l, 19.12 mg/l, and 25.50 mg/l, respectively. BOD values at three points are 9.02 mg/l, 16.11 mg/l and 20.94 mg/l.